APLIKASI METRIK SIGMA DALAM PEMANTAPAN MUTU INTERNAL PADA PEMERIKSAAN UREUM DISALAH SATU LABORATORIUM RUMAH SAKIT KABUPATEN PANGANDARAN - Rizal Apriansyah Pratama; Dewi Kania Yulianti; Doni Setiawan (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2021)
Intralaboratory Quality Control in clinical laboratories is significant and helps detect errors early to improve quality and guarantee examination results. The guaranteed method can be done by applying the sigma metric, which can detect 690,000 errors per million opportunities or 30.9 probability without defects with a minimum sigma value category of 3 and a maximum sigma value of 6. Urea is one of the clinical chemistry examination parameters that often has a sigma value <3. This study aims to determine the application of the sigma metric in internal quality assurance on urea examination in one of the Pangandaran district hospital laboratories. This research method is a descriptive-analytic based on the sigma value in internal quality assurance on urea examination in Pangandaran district hospital laboratories. Based on the study results, the value of sigma 3 - < 4 or marginal in March and May 2021 at the average control level while at the pathological control level increased from 2 sigma in March to 3 sigma in May 2021 said to be marginal.